¿Quién es el antropólogo o antropóloga? - Bizeul, Daniel (2025)
The anthropologist as a person often remains a blind spot. Yet it is the fit, more or less favorable or unfortunate, between a specific social context and a particular anthropologist that partly shapes the course and outcome of fieldwork. Hence the importance of mentioning the anthropologist’s biographical events and experiences, as well as his or her physical and relational characteristics, insofar as they have an impact throughout the work. Such information helps readers better assess the quality of the research. However, this form of self-analysis remains an uncertain exercise, without protocol or model. Drawing on the example of an immersive fieldwork I carried out between 1996 and 1999 within the National Front, a French far-right political party, I show how the research was facilitated by my Catholic and right-wing upbringing, and complicated by my intimate life with two men, one of whom was Black.